DISTRIBUTED HYDROLOGICAL MODELLING OF TOTAL DISSOLVED PHOSPHORUS TRANSPORT IN AN AGRICULTURAL LANDSCAPE, PART I: DISTRIBUTED RUNOFF GENERATION - Gérard-Marchant P.; Steenhuis T.S.; Hively W.D. (My University, 2006)
Successful implementation of best management practices for reducing non-point source (NPS) pollution requires knowledge of the location of saturated areas that produce runoff. A physically-based, fully-distributed, GIS-integrated model, the Soil Moisture Distribution and Routing (SMDR) model was developed to simulate the hydrologic behavior of small rural upland watersheds with shallow soils and steep to moderate slopes. The model assumes that gravity is the only driving force of water and that most overland flow occurs as saturation excess. The model uses available soil and climatic data, and requires little calibration. The SMDR model was used to simulate runoff production on a 164-ha farm watershed in Delaware County, New York, in the headwaters of New York City water supply. Apart from land use, distributed input parameters were derived from readily available data. Simulated hydrographs compared reasonably with observed flows at the watershed outlet over a eight year simulation period, and peak timing and intensities were well reproduced. Using off-site weather input data produced occasional missed event peaks. Simulated soil moisture distribution agreed well with observed hydrological features and followed the same spatial trend as observed soil moisture contents sampled on four transects. Model accuracy improved when input variables were calibrated within the range of SSURGO-available parameters. The model will be a useful planning tool for reducing NFS pollution from farms in landscapes similar to the Northeastern US.